Trade‐off between plant resistance and tolerance to herbivory: Mechanical defenses outweigh chemical defenses. Issue 1 (10th November 2022) - Salgado‐Luarte, Cristian; González‐Teuber, Marcia; Madriaza, Karina; Gianoli, Ernesto
Abstract: Plant resistance includes mechanical and chemical defenses that reduce herbivory, whereas plant tolerance reduces the fitness impact of herbivory. Because defenses are costly and investing in both resistance and tolerance may be superfluous, trade‐offs among them are expected. In forest ecosystems, the mechanical strengthening of leaves is linked both to shade adaptation and antiherbivore defenses, but it also compromises resource uptake, therefore limiting regrowth following damage, suggesting a trade‐off between mechanical defenses and tolerance. We tested for the resistance–tolerance trade‐off across 11 common tree species in a temperate rainforest and explored mechanistic explanations by measuring chemical and mechanical defenses. Herbivory damage was negatively associated with leaf toughness and fiber content, whereas there was no significant relationship between herbivory and secondary metabolites (flavonols, gallic acid, tannins, and terpenoids). We detected a resistance–tolerance trade‐off, as expected. We found a negative relationship between mechanical defenses and tolerance, estimated as the survival ratio between experimentally damaged and undamaged seedlings. Tolerance and secondary metabolites showed no significant association. Results suggest that selective forces other than herbivory acting on defensive traits can favor a resistance–tolerance trade‐off. Therefore, plant adaptation to contrasting light environments may contribute to the evolution of resistance–tolerance trade‐offs.